Контактное взаимодействие алмаз-алмаз при шлифовании кристалла алмаза - Астапчик, С.А.; Кузей, А.М.; Зайцев, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The mechanism of wearing a crystal natural diamond has been investigated during polishing of abrasive diamond tool. It is established that the major wearing mechanism is contact interaction of flat grain tips with a flat crystal surface. The crystal surface wearing occurs during failure of nanodimensional irregularities of defective surface layer.